Description of five new species and re-description of two species of Amblyseius (Acari: Phytoseiidae) from West Bengal, India - Karmakar, Krishna; Bhowmik, Sagarika; Sherpa, Choyang (Zootaxa, 2017)
In this paper five new mite species are described from West Bengal, India—Amblyseius dahliae sp. nov., A. bengalensis sp. nov., A. brachycalyx sp. nov., A. conulus sp. nov., A. parbatabasii sp. nov., and two species are re-described—Amblyseius largoensis (Muma, 1955) and A. herbicolus (Chant, 1959) (Acari: Phytoseiidae).